Development of low-nitrogen adapted rice lines under low-nitrogen selection environment - Puji Lestari, Angelita; 1, Suwarno; 1, Trikoesoemaningtyas; Sopandie, Didy; Aswidinnoor, Hajrial (The Indian Journal of Genetics and Plant Breeding, 2016)
A study was conducted on the materials derived from the crosses, Gampai/IR77674 and Progol/Asahan to evaluate the performance of lines selected through pedigree method of selection under adequate nitrogen (138 kg/ha) and low nitrogen (34.5 kg/ha) conditions. Similar doses of nitrogen were taken for evaluating (cultural environment) the selected lines. Selection was made from F3 to F5 generations under adequate and low nitrogen environments, then F6 was evaluated at Muara Experimental Farm in dry season 2014, using augmented design, with checks replicated thrice. Results showed higher values of panicle weight, panicle length and plant height. The method followed under selection environment, similar to target environment was suitable enough to obtain adapted rice lines for the target environment. It is suggested that to obtain low nitrogen adapted rice lines, selection in breeding program should be conducted under sub-adequate nitrogen conditions in field.